2013
DOI: 10.5688/ajpe7715
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Expectations for Entry-level Practitioner Competency

Abstract: Objective. To determine if defined subgroups of pharmacists' have variability in their expectations for competency of entry-level practitioners. Methods. Rating scale data collected from the 2009 National Pharmacy Practice Survey were analyzed to determine to what extent pharmacists' degree, practice setting, and experience as a preceptor were associated with the ratings they assigned to 43 competency statements for entry-level practitioners. The competency statements determine the content on the North America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…56 Another study revealed that pharmacists working in inpatient settings gave slightly higher ratings to the competency statements than did pharmacists working in outpatient settings, pharmacists without direct patient care responsibilities, and those in academia. 50 Pharmacists working in medical laboratories had the lowest scores, showing that pharmacists are not well prepared for this field upon graduation; in Lebanon, 3-4 additional years are required before entering this field of work. Further research is necessary to confirm our results.…”
Section: 41mentioning
confidence: 99%
See 1 more Smart Citation
“…56 Another study revealed that pharmacists working in inpatient settings gave slightly higher ratings to the competency statements than did pharmacists working in outpatient settings, pharmacists without direct patient care responsibilities, and those in academia. 50 Pharmacists working in medical laboratories had the lowest scores, showing that pharmacists are not well prepared for this field upon graduation; in Lebanon, 3-4 additional years are required before entering this field of work. Further research is necessary to confirm our results.…”
Section: 41mentioning
confidence: 99%
“…This finding is consistent with that of a study showing that pharmacists with a doctor of pharmacy (PharmD) degree rated the competency statements higher in terms of criticality to entry-level practice than those with a bachelor of science (BS) degree did. 50 Similarly, a Thai study among hospital pharmacists showed that the hospital pharmacists holding a PharmD degree scored higher in competencies related to inpatient care, not in community and primary care settings due to the lack of skills in health promotion and humanistic aspects of pharmacy practice. 51 This point confirms the need to make the PharmD degree mandatory, similar to developed countries since the Advanced Pharmacy Practice Experiences seem to be crucial for the maturation of competencies before pharmacists graduate and enter the labor market.…”
Section: 41mentioning
confidence: 99%
“…-One institutional framework for cancer services; 69 and -Six other national frameworks specific for heart failure, 70 diabetes, 71 pharmacists with special interest, 72 medicines information, 73 critical care, 74 and medicines use review and prescribing intervention services. 75 Also included in this review were 22 studies that evaluated validity and/or applicability to practice of a competency framework in pharmacy 9,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] (this was in addition to the articles by Kennie-Kaulbach et al 59 and Carrington et al 69 that also reported the validation results of their respective frameworks) (Table 3). Of the 22 studies, the majority (n=10, 45%) were articles that evaluated the validity/applicability of a generic, sector/role-related, or specialty-specific framework in United Kingdom 76,80-82,88 , Croatia 9,93 , and other countries in Europe 83,86,94 (Table 3); Others were studies conducted in Australia 69,78,84,91 (Western Pacific); Japan 90 , Kuwait 89 (Eastern Mediterranean); USA 87 , Canada 59 (the Americas); Thailand 79 (South East Asia); and Africa (included Ghana, Kenya, Nigeria, South Africa and ten other countries in the region) 85…”
Section: IImentioning
confidence: 99%
“…75 Also included in this review were 22 studies that evaluated validity and/or applicability to practice of a competency framework in pharmacy 9,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] (this was in addition to the articles by Kennie-Kaulbach et al 59 and Carrington et al 69 that also reported the validation results of their respective frameworks) (Table 3). Of the 22 studies, the majority (n=10, 45%) were articles that evaluated the validity/applicability of a generic, sector/role-related, or specialty-specific framework in United Kingdom 76,80-82,88 , Croatia 9,93 , and other countries in Europe 83,86,94 (Table 3); Others were studies conducted in Australia 69,78,84,91 (Western Pacific); Japan 90 , Kuwait 89 (Eastern Mediterranean); USA 87 , Canada 59 (the Americas); Thailand 79 (South East Asia); and Africa (included Ghana, Kenya, Nigeria, South Africa and ten other countries in the region) 85 (Table 3). One other literature evaluated the FIP global framework in 64 countries 77 , while another evaluated the transnational applicability of two generic national frameworks 92 (Table 3).…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation